Engaging radicals in transition metal-catalyzed cross-coupling with alkyl electrophiles : recent advances - Kaga, Atsushi (2022)
Transition metal-catalyzed cross-coupling reactions have created an epoch in modern synthetic organic chemistry, offering a variety of insights into retrosynthetic tactics for synthesizing targeted complex molecules in medicine and materials-based applications. Despite numerous types of combinations of nucleophiles, electrophiles, and transition metal catalysts available for the cross-coupling reactions, construction of covalent bonds that include sp3-hybridized carbon(s) remains a challenge because of the inherent diverse reactivity of the alkyl species (i.e., alkyl halides and alkyl metals) involved in the catalytic cycle. Methods for leveraging alkyl radicals have recently emerged, which will aid in the realization of this goal. This perspective highlights and discusses recent advances in transition metal-catalyzed cross-coupling reactions that engage alkyl radicals for C(sp3)-N and C(sp3)-Si bond formation with alkyl halides as well as use of carboxylic acid derivatives as surrogates of alkyl halides in decarboxylative C(sp3)-C(sp2)/C(sp3)/B couplings.